2019
DOI: 10.3389/ffgc.2019.00073
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Soil Microbial Communities Show Signs of Increasing Phosphorus Limitation in Two Temperate Forests After Long-Term Nitrogen Addition

Abstract: C:N stoichiometry, we further show that microbial communities responded in part nonhomeostatically to decreasing resource C:N, in addition to a likely increase in their carbon use efficiency and a decrease in nitrogen use efficiency. While the expected increased allocation to C-and decreased allocation to N-acquiring enzymes was not found, microbial investment in P acquisition (acid phosphatase activity) increased in the nutrient-poor Podzol (but not in the nutrient-rich Gleysol). Enzyme vector analysis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 121 publications
(203 reference statements)
1
10
0
Order By: Relevance
“…All these mentioned reasons explain why we found no or only minor changes of the soil microbial communities to the moderate long-term N addition at this forest site. The bacterial and fungal abundance remained unchanged, which is in agreement with others (Peng et al, 2017;Forstner et al, 2019b). Similarly, Hesse et al (2015) found no change in fungal biomass in a natural maple forest in USA treated with N for 16 years.…”
Section: Long-term N Addition Effects On Soil Microbial Communitiessupporting
confidence: 89%
See 2 more Smart Citations
“…All these mentioned reasons explain why we found no or only minor changes of the soil microbial communities to the moderate long-term N addition at this forest site. The bacterial and fungal abundance remained unchanged, which is in agreement with others (Peng et al, 2017;Forstner et al, 2019b). Similarly, Hesse et al (2015) found no change in fungal biomass in a natural maple forest in USA treated with N for 16 years.…”
Section: Long-term N Addition Effects On Soil Microbial Communitiessupporting
confidence: 89%
“…In temperate and boreal forests, reactive N inputs have been shown to alter tree growth and understory biomass, sometimes positively, sometimes negatively, depending on the N status, and other site factors (Solberg et al, 2009;Thomas et al, 2010;Gundale et al, 2014;Forstner et al, 2019a). N deposition can further accelerate soil acidification and base cation loss (Carnol et al, 1997;Högberg et al, 2006;Forstner et al, 2019a), increase N leaching (Carnol et al, 1997;Moldan and Wright, 2011;Schleppi et al, 2017), favor forest nutritional imbalances (Mooshammer et al, 2014;Zechmeister-Boltenstern et al, 2015;Forstner et al, 2019b) and affect the cycling and storage of soil organic C (Treseder, 2008;Janssens et al, 2010;Maaroufi et al, 2015). N deposition can also accelerate microbial soil processes that are part of the N cycle, such as nitrification and denitrification (Gundersen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not have respiration data for the plots supplemented with P, but we speculate that the higher C stock is a result of further reduced decomposition. When N limitation is alleviated by fertilization, P may become a limiting factor (Aber et al 1989;Braun et al 2010) that could stimulate microbial decomposers to mine P from organic matter (Forstner et al 2019;Widdig Fig. 3 Model estimates of treatment effects on soil respiration, calculated on a per area (R s ) basis, are adjusted for variation in soil temperature and water content.…”
Section: Discussionmentioning
confidence: 99%
“…Under low N deposition, however, Clemmensen et al (2021) also suggested a tipping point in belowground C sequestration from tundra to subalpine forests mediated by changed functionality of EM communities, but the existence of thresholds and positive feedbacks that generate such drastic changes was not discussed. Furthermore, Jassey et al (2018) showed how drought generated aerobic conditions that, by favouring saprotrophic fungi over bacteria and enhancing decomposition and nutrient mineralization, transformed a moss and ericoid-dominated bog into a graminoid-dominated ecosystem; and Forstner et al (2019) described how long-term N addition caused changes in saprotrophic fungal C, N and phosphorus (P) use efficiencies, and suggested that microbial P limitation could ultimately lead to a tipping point.…”
Section: Ecosystem Tipping Pointsmentioning
confidence: 99%